Leadership Strategy to Improve Lecturer Professionalism - Saefrudin; Jaelani, Dian Iskandar (LETIGES, 2024)
Leadership in higher education has a strategic role in developing the professionalism of lecturers, especially in the Islamic higher education environment. The purpose of this study is to analyze leadership strategies in higher education and policies implemented to develop the professionalism of lecturers based on religious values. The study was conducted in two universities, UNHASY and UNIPDU. The type of research uses qualitative with a case study approach. Data collection involves observation, interviews, and documentation. Primary data was obtained from research subjects, namely the rector and lecturers, while secondary data was in public and private documents. Thematic data analysis techniques and data validity use triangulation techniques. The study results show that UNHASY and UNIPDU have a basic transformational leadership style but have different approaches. UNHASY applies leadership based on religious values ​​, focusing on character and ethical development. At the same time, UNIPDU adopts leadership that is more adaptive to global change and integrates religious practices with technological developments. Both leadership models significantly impact lecturer professionalism, as seen in competence in teaching, the use of technology, and the ability to be a moral role model. This study recommends the importance of developing visionary and responsive leadership to global change and the need to integrate ethical values ​​in developing lecturer professionalism. The implications of this study in the context of higher education confirm that supportive and participative leadership styles are essential for a thriving academic environment. Leadership styles must also be adjusted to the cultural context and values ​​that exist in each institution. This study also contributes to the development of the lecturer's professionalism theory. The findings suggest that effective higher education leadership contributes directly to improving the quality of lecturers' work, which includes innovation in teaching and achieving research targets.